Marco Aguilar: The Immortal Poet in Espino Blanco - Coto Molina, Walter (2024)
By the initiative of its owner, lawyer and philosopher Walter Coto, the facilities of the Espino Blanco Biological Reserve hosted a gathering to commemorate the life and work of poet Marco Aguilar, just a few days after his passing. The event included the placement of a memorial plaque with his name on a corpulent fosforillo tree (Dendropanax arboreus) in the Calzada de los Poetas (Causeway of the Poets), in the middle of the forest, as Coto describes in this article.